SISTEM INFORMASI INVENTARIS BARANG DI PT. BPR BANK JEPARA ARTHA - Setiawan, Budi; Mahendra, Danang; Subhan Akbar, Agus (Universitas Islam Nahdlatul Ulama Jepara, 2023)
Inventory data management at PT. BPR BANK JEPARA ARTHA is still being carried out by recording data on paper and then copying it into excel so that to search for data it needs to be checked one by one. With this inventory information system, it helps companies to see the calculation of the value of assets that have been determined by the percentage of depreciation value based on the economic value of an item. The results of the study show that to calculate the book value of an item, it is necessary to know its economic value and then it is calculated starting from the initial purchase up to the specified month and year.